Production Systems and Supply Chain Management in Emerging Countries: Best Practices Selected papers from the International Conference on Production Research (ICPR) - Mejía, Gonzalo; Velasco, Nubia (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The book presents several highly selected cases in emerging countries where the production-logistics systems have been optimized or improved with the support of mathematical models. The book contains a selection of papers from the 5th International Conference on Production Research (ICPR) Americas 2010 held on July 21-23 in Bogotá, Colombia. The main topic of the conference was "Technologies in Logistics and Manufacturing for Small and Medium Enterprises" which is perfectly aligned with the realities of emerging countries. The book presents methodologies and case studies related to a wide variety of production/logistics systems such as diary production, auto parts, steel and iron production, and financial services. It is focused but not limited to Small/Medium Enterprises.